Benchmarking of Monte Carlo flux simulations of electrons in CO2. (10th November 2020) - Vialetto, L; Viegas, P; Longo, S; Diomede, P
Abstract: Electron velocity distribution functions (EVDFs) in CO2 obtained by means of the Monte Carlo flux (MCF) method are compared with results from two-term and multi-term Boltzmann solvers. The MCF method provides detailed calculations of the EVDF through a highly efficient variance reduction technique. Benchmark calculations of Legendre polynomial coefficients of the EVDF expansion are reported for a wide range of reduced electric fields ( E / N ), showing excellent agreement with multi-term solutions. Rate coefficients of inelastic processes calculated from two-term Boltzmann solvers differ significantly, up to 70%, from MCF and multi-term solutions, due to the anisotropy of the EVDF. An extension of the method to consider the thermal distribution of the background gas is also presented. This extension, together with an accurate description of the population of rotationally and vibrationally excited states, provides excellent agreement with measured transport coefficients at low E / N . A good agreement is obtained at moderate E / N between experimental values of dissociation rate coefficients and MCF calculations after careful consideration and analysis of several cross sections data sets.